2005
DOI: 10.1097/01.jnen.0000190066.13312.8f
|View full text |Cite
|
Sign up to set email alerts
|

Subventricular Zone Neuroblasts Emigrate Toward Cortical Lesions

Abstract: Adult subventricular zone (SVZ) neuroblasts migrate in the rostral migratory stream to the olfactory bulbs. Brain lesions generally increase SVZ neurogenesis or gliogenesis and cause SVZ cell emigration to ectopic locations. We showed previously that glia emigrate from the SVZ toward mechanical injuries of the somatosensory cerebral cortex in mice. Here we tested the hypotheses that SVZ neurogenesis increases, that neuroblasts emigrate, and that epidermal growth factor expression increases after cortical injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 53 publications
9
107
4
Order By: Relevance
“…In contrast to the results gained from cortical DCX-deficient neurons, which exhibited delayed maturation rate (Ackman et al, 2009), we found that ectopic mutant neurons display anticipated maturation of their functional properties, at least for some parameters. For instance, at 7 dpe in the RMS, these injury, likely through an epidermal growth factor pathway (Sundholm-Peters et al, 2005). This emphasizes how important it is to characterize what endogenous factors modulate the migration of neuronal precursors and, thus, control cell fate.…”
Section: Ectopic Neurons Exhibit Unique Featuresmentioning
confidence: 99%
“…In contrast to the results gained from cortical DCX-deficient neurons, which exhibited delayed maturation rate (Ackman et al, 2009), we found that ectopic mutant neurons display anticipated maturation of their functional properties, at least for some parameters. For instance, at 7 dpe in the RMS, these injury, likely through an epidermal growth factor pathway (Sundholm-Peters et al, 2005). This emphasizes how important it is to characterize what endogenous factors modulate the migration of neuronal precursors and, thus, control cell fate.…”
Section: Ectopic Neurons Exhibit Unique Featuresmentioning
confidence: 99%
“…Analogous flexibility of stem cell progeny fate is also apparent in the brain. Normally, SVZ NSCs generate new interneurons that populate the olfactory bulb; however, upon damage to the mouse cerebral cortex, neurogenesis increases and neuroblasts migrate to the site of injury (Magavi et al 2000;Parent et al 2002;Goings et al 2004;Sundholm-Peters et al 2005). In the Drosophila ovary, each GSC normally divides asymmetrically to self-renew and to form a more differentiated cystoblast; upon GSC loss, however, the remaining GSC can divide symmetrically to generate two GSCs (Xie and Spradling 2000).…”
Section: Stem Cells Respond To the Surrounding Tissuementioning
confidence: 99%
“…Post-trauma neurogenesis in the brain cortex of adult mammals is given an increasing attention (Gu et al 2000, Jiang et al 2001, Jin et al 2003, Sundholm-Peters et al 2005, Ohira et al 2010. Most recent data not only evidence an influx to the traumatized region of immature neural cells from the SVZ and dentate gyrus, but also indicate to a possibility for in situ neurogenesis in the peri-injury zone.…”
Section: Discussionmentioning
confidence: 99%